Empowering Educators: Exploring Strategies for Research Engagement - G. Lopez, Reshyl; Monkonsawasd, Poonkeat (Jurnal Pendidikan dan Profesi Keguruan, 2026)
Objective: This action research examined barriers to faculty research engagement and evaluated institutional strategies to improve participation in a private higher education institution in Bukidnon, Philippines. Method: An embedded mixed-methods design combined descriptive statistics to map baseline research participation with phenomenological inquiry to explore educators lived experiences. Data were collected from five purposively selected faculty members through questionnaires, focus group discussions, and action research cycles of reflection, intervention, and evaluation. Results: Prior to the intervention, no research proposals were submitted during the preceding academic year. Following the implementation of financial incentives, workload adjustments, and research skills enhancement seminars, four research proposals were produced across two academic departments. Qualitative findings identified seven major barriers, including limited research training, workload constraints, insufficient institutional support, and negative perceptions toward research. Novelty: Unlike prior studies that primarily document barriers to faculty research engagement, this study empirically demonstrates how targeted institutional interventions within an action research framework can produce measurable improvements in research participation in private higher education contexts.